Navigating the Return-to-Work Experience for New Parents Maintaining Work-Family Well-Being - Anett Rusznák; Zsófia Kocsis (Central European Journal of Educational Research)
Bibliography of the reviewed book: Karanika-Murray, M., & Cooper, C. (Eds.). (2020). Navigating the Return-to-Work Experience for New Parents: Maintaining Work-Family Well-Being (1st ed.). Routledge.